A Study Of Literary Psychology: Characteristics Of The Main Character In The Monologue Script “Tolong” By Nano N. Riantiarno And The Monologue Script “Marsinah Menggugat” By Ratna Sarumpaet - Aryadi, DC; Mualimah, Eka (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The author found the psychological conditions in the two main characters, namely Atika in the monologue scrip Tolong and Marsinah in the monologue teks Marsinah Menggugat. This study uses the method of literary psychology by analyzing each main character built in the script. This study discusses : 1. How is Atikah's psychologi conditional in the monologue bantu? 2. How is Atikah's psychology condition in the monologue text Marsinah Menggugat? 3. What is the psychology relationship between Atikah in the monologue Tolong and Marsinah in the monologue Marsinah Menggugat? This study uses a literary pschlologi approach, namely : 1) Expressive approach examining the pscychological aspects of the authour in the creative proses project throught his creation 2) textual approach, namely examining the psychological aspects of characters in literary works. In this study it can be concluded. Likewise with the entitled